2013
DOI: 10.1007/s00134-013-2879-y
|View full text |Cite|
|
Sign up to set email alerts
|

Is treatment with a high flow nasal cannula effective in acute viral bronchiolitis? A physiologic study

Abstract: HFNC with a flow rate equal to or above 2 L/kg/min generated a clinically relevant PP, with improved breathing pattern and rapid unloading of respiratory muscles, in young infants with acute RSV bronchiolitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
173
0
17

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 188 publications
(196 citation statements)
references
References 28 publications
6
173
0
17
Order By: Relevance
“…In a prospective observational study, KRIVEC et al [120] enrolled 39 children f24 months of age with acute viral bronchiolitis and showed that HFNC effectively improved physiological respiration and gas exchange variables. These results are in line with other recent clinical trials, which demonstrated improved breathing patterns and rapid respiratory muscle uploading after HFNC treatment for viral bronchiolitis in infants [121].…”
Section: Paediatric Intensive Caresupporting
confidence: 92%
“…In a prospective observational study, KRIVEC et al [120] enrolled 39 children f24 months of age with acute viral bronchiolitis and showed that HFNC effectively improved physiological respiration and gas exchange variables. These results are in line with other recent clinical trials, which demonstrated improved breathing patterns and rapid respiratory muscle uploading after HFNC treatment for viral bronchiolitis in infants [121].…”
Section: Paediatric Intensive Caresupporting
confidence: 92%
“…126 There is evidence that high-flow nasal cannula improves physiologic measures of respiratory effort and can generate continuous positive airway pressure in bronchiolitis. [127][128][129][130] Clinical evidence suggests it reduces work of breathing 131,132 and may decrease need for intubation, [133][134][135][136] although studies are generally retrospective and small. The therapy has been studied in the ED 136,137 and the general inpatient setting, 134,138 as well as the ICU.…”
Section: Action Statement Profile Kas 6bmentioning
confidence: 99%
“…7 Flow rates of ≥6 L/min were associated with positive pharyngeal pressures throughout the respiratory cycle. Another study in infants with bronchiolitis found a linear association between increasing HHHFNC therapy flow rates and nasopharyngeal pressure, with a reduction in the rate of increase in pressure with flow rates >6 L/min.…”
Section: Mechanisms Of Action Of Hhhfnc Therapymentioning
confidence: 97%